2007
DOI: 10.1002/dneu.20316
|View full text |Cite
|
Sign up to set email alerts
|

Greater hippocampal neuronal recruitment in food‐storing than in non‐food‐storing birds

Abstract: Previous research has shown heightened recruitment of new neurons to the chickadee hippocampus in the fall. The present study was conducted to determine whether heightened fall recruitment is associated with the seasonal onset of food-storing by comparing neurogenesis in chickadees and a non-food-storing species, the house sparrow. Chickadees and house sparrows were captured in the wild in fall and spring and received multiple injections of the cell birth marker bromodeoxyuridine (BrdU). Birds were held in cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 26 publications
4
37
0
Order By: Relevance
“…As a result, the fact that only 54 per cent of doublecortinpositive cells also labelled for BrdU may reflect an increase in new neurons and hence a lower proportion of BrdU-labelled cells among doublecortin-positive cells. Hoshooley & Sherry (2007) found that, in chickadees, only one-third of BrdU-positive cells also expressed NeuN after six weeks. Expression of NeuN closely follows cessation of doublecortin expression (Brown et al 2003) and thus it is likely that doublecortin expression in birds lasts for up to six weeks or more.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the fact that only 54 per cent of doublecortinpositive cells also labelled for BrdU may reflect an increase in new neurons and hence a lower proportion of BrdU-labelled cells among doublecortin-positive cells. Hoshooley & Sherry (2007) found that, in chickadees, only one-third of BrdU-positive cells also expressed NeuN after six weeks. Expression of NeuN closely follows cessation of doublecortin expression (Brown et al 2003) and thus it is likely that doublecortin expression in birds lasts for up to six weeks or more.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the survival of new brain cells is enhanced by spatial navigation learning during Morris water maze tests in rats and mice [reviewed in Shors, 2008;Shors et al, 2012]. Similarly, Hoshooley and Sherry [2007] showed that greater neuron recruitment in the hippocampus is associated with food caching in adult black-capped chickadees, i.e. Poecile atricapillus [also see review in Sherry and Hoshooley, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…If it is the encoding of new memories that is important for this increased neuronal survival, then this explanation only works if hoarding intensity is still relatively high during the first weeks after injection. It is important to note that neurons appear to mature much faster in rats than in chickadees as a marker for mature neurons (NeuN) is expressed in more than 50 per cent of all newly generated hippocampal cells already at 21 days in rats (Brown et al 2003), whereas in black-capped chickadees only about one-third of six-week-old newly generated cells expressed NeuN (Hoshooley & Sherry 2007). Such a potential later neuronal maturation in chickadees could shift forward the importance of learning on neuronal survival.…”
Section: Mechanisms Underlying Hippocampal Memory Processingmentioning
confidence: 99%